Dari Poro hingga Paketik: AKTIVITAS Ekonomi Orang Kalang di KOTAGEDE pada masa depresi-1930 - Mutiah Amini (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2006)
The aim of this article is to discuss The Kalang People in Tegalgendu, Kotagede in the Depression era. In historical term, depression era is the time when all of the society have difficulties economically. Unlike the common people, The Kalang people can solve that problem by working as a juragan in Poro and Paketik. Poro means retailer or agent of everything and paketik means someone who owns a pawnshop. By reading this article we can know deeply what activities of Kalang people did during the depression era, and why Kalang people chose to become Poro and Paketik in their economic activities. Further, we can learn how Kalang people teach their skills to the next generation.